Calcium Extract Characterization from Rajungan Crab Shell (Portunus pelagicus) and Bakau Crab Shell (Scylla serrata) using Calcination as Effervescent - Mohammad R. Usman; Muhamad D. Permana; Aditya F. Ardinsyah; Mega T. Wulandari; Aliyah Purwanti; Lindawati Setyaningrum; Ima F. Lestari; Stephanie D. Artemisia (Jurnal Akademika Kimia, 2022)
One of the prevention of osteoporosis is by taking calcium supplements. Crab shells are calcium sources that can be processed into supplements. Calcium extraction used the calcinations method at 900°C temperature for 4 hours. After calcining the crab shell powder, it was analyzed by using XRD and processed with the Highscore Plus application by using Rietveld method. The best calcium crystals will be used as raw material for effervescent powder. The results showed that calcium crystals from rajungan crab shells contained 0.4% CaCO3 with a crystallite size of 25.9001 nm and 99.6% CaO with a crystallite size of 82.7183 nm with a GoF value of 1.69979. Calcium crystals produced from bakau crab shells were 100% CaO with a crystallite size of 77.3397 nm with a GoF value of 1.90266. Calcium crystals from bakau crab shells were used as effervescent raw materials with 2 different formulations. The results of the organoleptic test from both effervescents showed the same results, namely in the form of a pale yellow powder with a orange scent and sour taste The results of the dispersion time test showed that the 2 formulations had met the requirements with the dispersion time of formula 1 being 31.67 seconds and formula 2 being 32.33 seconds. The results of the water content test of the two formulas met the requirements with the water content of formula 1 being 0.071% and formula 2 being 0.067%.